Fisetin Alleviated Bleomycin-Induced Pulmonary Fibrosis Partly by Rescuing Alveolar Epithelial Cells From Senescence - Zhang, Li; Tong, Xiang; Huang, Jizhen; Wu, Man; Zhang, Shijie; Wang, Dongguang; Liu, SiTong; Fan, Hong (Frontiers in Pharmacology, 2020)
Idiopathic pulmonary fibrosis (IPF) is an aging-associated disease, satisfactory therapies are not yet available. Accelerated senescence of alveolar epithelial cells plays an important part in IPF pathogenesis. Fisetin (FIS) is a natural non-toxic flavonoid, which has many pharmacological functions. However, the role of FIS in pulmonary fibrosis (PF) has not been established. In this study, we found that FIS treatment apparently alleviated BLM-induced weight loss, inflammatory cells infiltration, inflammatory factors expression, collagen deposition and alveolar epithelial cell senescence, along with AMPK activation and the down regulation of NF-κB and TGF-β/Smad3 in vivo. In vitro, FIS administration significantly inhibited the senescence of alveolar epithelial cells and senescence-associated secretory phenotype (SASP), followed by reduced transdifferentiation of fibroblasts to myofibroblasts as well as collagen deposition in fibroblasts, which was blocked by an AMPK inhibitor, Compound C. Together, these results suggest that FIS can alleviate the development of BLM-induced pulmonary fibrosis, which is related to the inhibition of TGF-β/Smad3 signaling and the reduction of alveolar epithelium cell senescence by regulating AMPK/NF-κB signaling pathway. FIS may be a promising candidate for patients with PF.